Coated polymer hydrogel as well as preparation method and application thereof
By introducing cement hydrated product nanoparticles and latex outer film layer into the polymer hydrogel, the problem of insufficient strength and toughness in a high load environment is solved, and the effects of high strength, high toughness and long service life are achieved.
Patent Information
- Application Number
- CN202411581052.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-11
AI Technical Summary
Existing polymer hydrogels lack mechanical strength and toughness in high load environments, and changes in water content affect their performance, resulting in poor water retention and short service life.
By introducing cement hydrated product nanoparticles into the polymer monomer, physical crosslinking points are formed to improve strength and toughness, and latex is applied to the surface of the hydrogel matrix to form an outer film layer, enhancing water retention and resistance to external damage.
It realizes the high strength, high toughness, high water retention and long service life of polymer hydrogels, and is suitable for applications in high load environments.
Smart Images

Figure CN119591919A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a film-coated polymer hydrogel and a preparation method and application thereof. Background Art
[0002] Polymer hydrogels are a class of materials composed of cross-linked polymers with a large number of pore structures inside that can absorb and retain a large amount of water. Polymer hydrogels are often prepared by polymerization or cross-linking reactions of monomers, and their physical and chemical properties can be adjusted by changing their components, degree of cross-linking and structure. Therefore, researchers can customize polymer hydrogels according to the needs of specific applications. For example, polymer hydrogels with good biocompatibility are one of the ideal choices for tissue engineering and drug delivery materials. In addition, polymer hydrogels have a high swelling ratio and extremely high water content, which makes them soft and elastic, and are widely used in software robots, wearable devices, artificial joints and other fields. However, it is precisely because of their high swelling ratio and high water content that polymer hydrogels usually have lower mechanical strength and toughness, which limits their application in high-load environments.
[0003] In addition, the properties of polymer hydrogels, such as strength, toughness and stiffness, are greatly affected by their water content. For example, low water content will cause polymer hydrogels to shrink, weaken the activity of polymer chains, make it difficult to conduct reversible interchain interactions, and lead to a significant reduction in toughness. Summary of the invention
[0004] In order to overcome the problems of low strength, poor water retention and short service life of the polymer hydrogel in the above-mentioned prior art, one of the objectives of the present invention is to provide a film-coated polymer hydrogel, which has the characteristics of high strength and high water retention.
[0005] A second object of the present invention is to provide a method for preparing the above-mentioned film-coated polymer hydrogel.
[0006] The third object of the present invention is to provide an application of the above-mentioned film-coated polymer hydrogel.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a film-coated polymer hydrogel, comprising a polymer hydrogel matrix and an outer film layer; the outer film layer is coated on at least a portion of the surface of the polymer hydrogel matrix;
[0009] The polymer hydrogel matrix comprises the following preparation raw materials: polymer monomer, cement hydration product nanoparticles, initiator and water;
[0010] The raw material for preparing the outer film layer includes latex.
[0011] The present invention introduces cement hydration product nanoparticles into polymer monomers to provide physical crosslinking points between polymer molecular chains, thereby improving the strength and toughness of polymer hydrogels, and a weak network is formed by physical crosslinking, which is conducive to maintaining a high water content of the material; at the same time, nanoparticles with a high specific surface area can form strong hydrogen bonds with polymer molecular chains inside the hydrogel, enhance the crosslinking effect, and further improve the mechanical properties of the polymer hydrogel. In addition, the present invention forms a protective barrier by arranging an outer film layer made of latex on the surface of the hydrogel matrix, which can prevent the internal water from evaporating outwards and improve the water retention of the hydrogel, and can also prevent external factors from destroying the three-dimensional network structure inside the polymer hydrogel, significantly improving the service life of the hydrogel and expanding its application scenarios.
[0012] Preferably, the water content of the coated polymer hydrogel is 50 to 95%; more preferably 55 to 90%; and even more preferably 60 to 85%.
[0013] Preferably, the latex includes at least one of polyvinyl acetate latex, polybutadiene latex or styrene-butadiene latex; further preferably, the latex is selected from polyvinyl acetate latex.
[0014] Preferably, the polymer monomers include acrylamide monomers, acrylate monomers or a combination thereof.
[0015] Preferably, the acrylamide monomer includes at least one of acrylamide, methacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-isopropylacrylamide, N-methylacrylamide, N-hydroxyethylacrylamide or N-hydroxymethylacrylamide; further preferably, the acrylamide monomer includes at least one of acrylamide, methacrylamide, N,N-dimethylacrylamide or N,N-diethylacrylamide; further preferably, the acrylamide monomer is selected from acrylamide.
[0016] Preferably, the acrylate monomer includes at least one of magnesium acrylate, sodium acrylate, lithium acrylate, magnesium methacrylate, sodium methacrylate or lithium methacrylate; further preferably, the acrylate monomer includes at least one of magnesium acrylate, sodium acrylate or lithium acrylate; even more preferably, the acrylate monomer is selected from magnesium acrylate.
[0017] Preferably, the cement hydration product nanoparticles are formed by a hydration reaction between cement and water under the action of external mechanical force and low temperature conditions; the low temperature is -2 to 5°C.
[0018] Preferably, the external mechanical force includes ultrasound, stirring or a combination thereof; further preferably, the external mechanical force includes ultrasound and stirring.
[0019] Preferably, the low temperature is -1 to 3°C; more preferably, 0 to 2°C.
[0020] Preferably, the cement hydration product nanoparticles include calcium hydroxide nanoparticles.
[0021] Preferably, the cement includes at least one of fast-hardening Portland cement, ordinary Portland cement, slag Portland cement, pozzolanic Portland cement, fly ash Portland cement or composite Portland cement; further preferably, the cement is selected from fast-hardening Portland cement.
[0022] Preferably, the 28d compressive strength of the cement is ≥42.5MPa; more preferably ≥52.5MPa.
[0023] Preferably, the strength grade of the cement is 42.5, 42.5R, 52.5, 52.5R, 62.5 or 62.5R; further preferably, the strength grade of the cement is 52.5, 52.5R, 62.5 or 62.5R; further preferably, the strength grade of the cement is 52.5 or 52.5R.
[0024] The strength grade of cement refers to the minimum compressive strength achieved after 28 days of curing under standard conditions.
[0025] In some specific embodiments of the present invention, the cement is selected from 52.5R rapid hardening Portland cement produced by Macau Cement Co., Ltd.
[0026] Preferably, the mass ratio of the polymer monomer to the cement hydration product nanoparticles is 100:(0.1-5); more preferably, it is 100:(0.3-3); and even more preferably, it is 100:(0.5-2).
[0027] Preferably, the initiator includes at least one of a persulfate initiator, an azo initiator or a peroxide initiator; further preferably, the initiator is selected from a persulfate initiator; further preferably, the initiator includes at least one of ammonium persulfate, sodium persulfate or potassium persulfate.
[0028] Preferably, the mass ratio of the polymer monomer to the initiator is 100:(0.05-1); more preferably, it is 100:(0.08-0.8); and even more preferably, it is 100:(0.1-0.5).
[0029] Preferably, the mass ratio of the polymer monomer to the water is 100:(100-1000); more preferably, it is 100:(150-800); and even more preferably, it is 100:(200-600).
[0030] Preferably, the raw materials for preparing the polymer hydrogel matrix also include a co-initiator.
[0031] Preferably, the co-initiator is selected from amine co-initiators; further preferably, the co-initiator includes at least one of tetramethylethylenediamine, tetraethylethylenediamine, triethanolamine or triisopropanolamine; further preferably, the co-initiator includes tetramethylethylenediamine, tetraethylethylenediamine or a combination thereof.
[0032] Preferably, the mass ratio of the polymer monomer to the co-initiator is 100:(0.05-1); more preferably, it is 100:(0.08-0.8); and even more preferably, it is 100:(0.1-0.5).
[0033] In some specific embodiments of the present invention, the raw materials for preparing the polymer hydrogel matrix also include a cross-linking agent.
[0034] The addition of a crosslinking agent has little effect on the water retention of the hydrogel, but will affect the tensile strength and elongation recovery rate of the hydrogel. The crosslinking agent is beneficial to improve some strength and hardness, but it is more likely to break or crack during the stretching or compression process. Therefore, in order to pursue high strength and high toughness of the hydrogel, a crosslinking agent is generally not added. In some specific embodiments of the present invention, the addition of a crosslinking agent can adjust the performance of the hydrogel.
[0035] Preferably, the cross-linking agent is selected from acrylamide cross-linking agents; further preferably, the cross-linking agent is selected from N,N-methylenebisacrylamide.
[0036] Preferably, the mass ratio of the polymer monomer to the cross-linking agent is 100:(0.05-1); more preferably, it is 100:(0.08-0.8); and even more preferably, it is 100:(0.1-0.5).
[0037] Introducing a crosslinking agent (such as N,N-methylenebisacrylamide) into the polymer hydrogel of the physical crosslinking system can significantly improve the mechanical properties of the hydrogel. The hydrogel structure formed after the introduction of the crosslinking agent is composed of two different network structures interwoven with each other, including a strong network of chemical crosslinking and a weak network of physical crosslinking. Among them, the strong network provides strength to the polymer hydrogel, while the weak network maintains a high water content, thereby giving the hydrogel higher strength, but it is more likely to break or crack during stretching or compression. Therefore, the crosslinking agent can be added or not according to actual needs to balance the comprehensive performance of the hydrogel.
[0038] The second aspect of the present invention provides a method for preparing a film-coated polymer hydrogel, comprising the following steps: mixing polymer monomers, cement, initiator and water under the action of mechanical external force and low temperature conditions, wherein the low temperature is -2 to 5°C; then heating to carry out a polymerization reaction to obtain a polymer hydrogel matrix; applying latex on the surface of the polymer hydrogel matrix to form an outer film layer to obtain the film-coated polymer hydrogel as described in the first aspect of the present invention.
[0039] When cement and water are mixed, they react to form hydration products such as calcium hydroxide. When mixed under mechanical external force and low temperature conditions, nanoscale hydration products, namely cement hydration product nanoparticles, are formed. These nanoparticles can provide physical crosslinking points between polymer molecular chains, thereby improving the strength and toughness of polymer hydrogels. In addition, using the above method, the generation process of nanoparticles and the polymerization process of monomers are carried out simultaneously. On the one hand, this is conducive to the generation of more physical crosslinking points inside the polymer gel and improves performance; on the other hand, the one-pot method is used for preparation, which makes the process simpler, easier to operate and reduces time costs.
[0040] Preferably, when the raw materials for preparing the polymer hydrogel matrix further include a co-initiator and / or a cross-linking agent, the co-initiator and / or the cross-linking agent are mixed with the polymer monomer, cement, the initiator and water under the action of external mechanical force and low temperature conditions.
[0041] Preferably, the mass ratio of the polymer monomer to the cement is 100:(0.1-5); more preferably, it is 100:(0.3-3); and even more preferably, it is 100:(0.5-2).
[0042] Preferably, the external mechanical force includes ultrasound, stirring or a combination thereof; further preferably, the external mechanical force includes ultrasound and stirring.
[0043] Preferably, the low temperature is -1 to 3°C; more preferably, 0 to 2°C.
[0044] Preferably, the mixing time is 5 to 20 minutes; more preferably, it is 8 to 15 minutes.
[0045] Preferably, after the mixing, the mixture is placed under the low temperature conditions for 48 to 72 hours; more preferably, for 54 to 66 hours.
[0046] Preferably, the polymerization reaction temperature is 15 to 35°C; more preferably 18 to 32°C; and even more preferably 20 to 30°C.
[0047] Preferably, the polymerization reaction time is 1 to 15 hours; more preferably 2 to 10 hours; and even more preferably 4 to 8 hours.
[0048] Preferably, the polymerization reaction is carried out under vacuum conditions.
[0049] Preferably, the method of applying latex on the surface of the polymer hydrogel matrix includes at least one of coating, spraying or infiltration; further preferably, the method of applying latex on the surface of the polymer hydrogel matrix is selected from infiltration, that is, the polymer hydrogel matrix is immersed in latex; further preferably, the number of infiltrations is 2 to 10 times, more preferably 3 to 7 times.
[0050] The third aspect of the present invention provides a use of the coated polymer hydrogel described in the first aspect of the present invention in the preparation of tissue engineering materials, drug delivery materials, software robots, wearable devices or artificial joints.
[0051] The beneficial effects of the present invention are as follows: the present invention introduces nanoparticles of cement hydration products into polymer monomers, which is beneficial to the formation of physical cross-linking to improve mechanical properties and water retention, and combines with an outer film layer made of latex to achieve high water content and stable performance of the hydrogel, thereby obtaining a coated polymer hydrogel material with high strength, good toughness, good water retention and long service life.
[0052] Specifically, compared with the prior art, this application has the following advantages:
[0053] 1. Compared with ordinary hydrogels without cement hydration product nanoparticles, the coated polymer hydrogel of the present application has better mechanical properties, with a tensile strength of up to 400 kPa and a compressive strength of more than 90 MPa, and can maintain a basically unchanged shape with a deformation rate of only 6.4%.
[0054] 2. After repeated stretching, the coated polymer hydrogel of the present application has a good shape recovery effect and a low deformation rate. Except for the first stretching, the deformation rates of other stretchings are kept below 10%.
[0055] 3. Compared with the uncoated polymer hydrogel, since the surface of the coated polymer hydrogel of the present application is covered with a latex film formed by polyvinyl acetate emulsion, its water retention rate is still above 99% after 30 days, which is conducive to the stable maintenance of various properties of the polymer hydrogel and a significant extension of its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is the SEM image of the hydrogel of Example 1.
[0057] Figure 2 This is the infrared spectrum of the hydrogel of Example 1.
[0058] Figure 3 The tensile strength-strain curves of the hydrogels of Example 1 and Comparative Examples 1-2.
[0059] Figure 4 This is the cyclic tensile strength-strain curve of the hydrogel in Example 1.
[0060] Figure 5 A partial enlarged view of the cyclic tensile strength-strain curve of the hydrogel in Example 1
[0061] Figure 6 The compressive strength-strain curves of the hydrogels of Example 1 and Comparative Examples 1-2.
[0062] Figure 7 The morphology of the hydrogels of Example 1 and Comparative Example 2 after compression.
[0063] Figure 8 The water retention rate change curves of the hydrogels of Examples 1 to 4 and Comparative Example 1 within 30 days are shown.
[0064] Fig. 9 It is a partial enlarged view of the water retention rate change curve of the hydrogels of Examples 1 to 4 and Comparative Example 1 within 30 days. DETAILED DESCRIPTION
[0065] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0066] It should be noted that some of the raw material information used in the examples and comparative examples of the present invention are as follows:
[0067] Rapid hardening Portland cement was purchased from 52.5R rapid hardening Portland cement produced by Macao Cement Co., Ltd.;
[0068] Acrylamide, magnesium acrylate, ammonium persulfate, sodium persulfate, and tetramethylethylenediamine were purchased from Shanghai Aladdin Reagent Company;
[0069] The latex is ordinary commercial transparent waterproof white latex paint (the main component is polyvinyl acetate emulsion).
[0070] Example 1
[0071] A coated polymer hydrogel, prepared by the following raw materials:
[0072]
[0073] The preparation process of the above-mentioned film-coated polymer hydrogel is as follows:
[0074] 1. Under ice bath conditions (0-2°C), add water and acrylamide to a beaker in sequence; after acrylamide is completely dissolved, add ammonium persulfate and tetramethylethylenediamine; then, turn on ultrasound and mechanical stirring;
[0075] 2. Under the action of ultrasound and mechanical stirring, add silicate cement slowly and close to the wall of the beaker. The whole adding process lasts about 30 seconds. Then, continue ultrasound and mechanical stirring stably for 10 minutes.
[0076] 3. While stirring, quickly dispense the solution in the beaker into the mold, seal it and place it in a refrigerator at 0-2℃ for three days;
[0077] 4. When the time is up, quickly transfer the mold containing the reaction liquid to a vacuum oven, evacuate the mold at room temperature for 4 to 8 hours, and wait for gelation;
[0078] 5. After demolding, the polyacrylamide hydrogel is obtained, which is soaked in latex for 3 to 7 times and air-dried in air at room temperature for 24 hours to form a film, thereby obtaining a coated polymer hydrogel with good water retention. The water content of the hydrogel obtained in this example is 80%.
[0079] Example 2
[0080] A coated polymer hydrogel, prepared by the following raw materials:
[0081]
[0082]
[0083] The preparation process of the above-mentioned film-coated polymer hydrogel is the same as that of Example 1.
[0084] The water content of the hydrogel obtained in this example is 60%.
[0085] Example 3
[0086] A coated polymer hydrogel, prepared by the following raw materials:
[0087]
[0088] Preparation process of the above-mentioned film-coated polymer hydrogel:
[0089] 1. Under ice bath conditions, add half of the formula amount of water (0-2°C) and half of the formula amount of magnesium acrylate to the beaker in sequence; when the magnesium acrylate is completely dissolved, add silicate cement to the beaker slowly and adhere to the wall. The whole adding process lasts about 30 seconds; then, continue to ultrasonicate and mechanically stir for 10 minutes;
[0090] 2. Add sodium persulfate and tetramethylethylenediamine to the other half of the water and magnesium acrylate, and after the solids are completely dissolved, pour into the ice bath beaker in step 1;
[0091] 3. After rapid stirring for 10 seconds, quickly dispense the solution in the beaker into the mold, seal it, and place it in a refrigerator at 0-2°C to wait for gelation;
[0092] 4. After demolding, the magnesium polyacrylate hydrogel is obtained, which is soaked in latex for 3 to 7 times and dried in air at room temperature for 24 hours to form a film, thereby obtaining a coated polymer hydrogel with good water retention.
[0093] The water content of the hydrogel obtained in this example is 60%.
[0094] Example 4
[0095] A coated polymer hydrogel, prepared by the following raw materials:
[0096]
[0097] The preparation process of the above-mentioned film-coated polymer hydrogel is the same as that of Example 1.
[0098] The water content of the hydrogel obtained in this example is 80%.
[0099] Comparative Example 1
[0100] A polymer hydrogel, which is different from Example 1 in that the hydrogel in this example is not coated, and the preparation method does not include step 5. Other raw materials and preparation steps are the same as those in Example 1.
[0101] Comparative Example 2
[0102] A common polyacrylamide hydrogel, prepared by the following raw materials:
[0103]
[0104] The preparation process of the above-mentioned ordinary polyacrylamide hydrogel is as follows: at room temperature (25°C), add acrylamide and water into a beaker. After the acrylamide is completely dissolved, add the remaining raw materials under mechanical stirring and disperse them evenly, and then pour the reaction mixture into the prepared mold. After the polymerization reaction is completely gelled, the ordinary polyacrylamide hydrogel can be demolded to obtain the ordinary polyacrylamide hydrogel.
[0105] Performance Testing
[0106] (1) The structures of the hydrogels in the examples and comparative examples were characterized by scanning electron microscopy (SEM) and infrared spectroscopy.
[0107] Figure 1 This is the SEM image of the hydrogel in Example 1. It can be seen that the hydrogel in Example 1 presents a three-dimensional network structure with a rich porous structure. Figure 2 is the infrared spectrum of the hydrogel of Example 1. Figure 2 It can be seen that 3415cm -1 The characteristic absorption peak of free -NH2 is 2922cm -1 It is the characteristic absorption peak of methylene (-CH2-) stretching vibration, 1677cm -1 The stretching vibration peak of the carbonyl group (C=O) in the amide structure is 1454 cm -1 The peak at the bottom is the deformation absorption peak of methylene (-CH2-), so it can be judged that the polyacrylamide hydrogel has been successfully prepared.
[0108] (2) The hydrogels of the embodiments and comparative examples were subjected to tensile tests and compression tests. Specifically, the sample size used for the tensile test was 3 cm, and the sample size used for the compression test was 1 cm. The test temperature was room temperature 25° C., and the humidity was 75%. The tensile speed and the compression speed were both 2 mm / min.
[0109] Figure 3 The tensile strength-strain curves of the hydrogels of Example 1 and Comparative Examples 1 to 2 are shown in FIG. Figure 3 It can be obtained that the deformation rate of Example 1 is 597%, the deformation rate of Comparative Example 1 is 586%, and the deformation rate of Comparative Example 2 is 516%. It can be seen that compared with Comparative Examples 1 to 2, the hydrogel of Example 1 has a higher deformation rate. The cyclic tensile properties of the hydrogel of Example 1 are further tested. Figure 4 is the cyclic tensile strength-strain curve of the hydrogel in Example 1, Figure 5 This is a partial enlarged view of the cyclic tensile strength-strain curve of the hydrogel in Example 1. Figures 4-5 It can be obtained that the deformation rate of the hydrogel in Example 1 is 18.3% in the first cycle, 5.9% in the second cycle, 3.1% in the third cycle, 2.4% in the fourth cycle, and 597% in the fifth cycle.
[0110] Figure 6 The compressive strength-strain curves of the hydrogels of Example 1 and Comparative Examples 1 to 2 are shown in FIG. Figure 6 It can be obtained that the deformation rate of Example 1 is 6.4%, the deformation rate of Comparative Example 1 is 6.1%, and the deformation rate of Comparative Example 2 is 94.8%. Figure 7The morphologies of the hydrogels of Example 1 and Comparative Example 2 after compression, wherein (A) is Example 1 and (B) is Comparative Example 2; Figure 7 It can be seen that compared with the common polyacrylamide hydrogel in Comparative Example 2, the hydrogel in Example 1 has better compression resistance and can avoid the destruction of the original morphology and structure after compression.
[0111] The specific data of the tensile strength and compressive strength of the hydrogels of Example 1 and Comparative Examples 1-2 are shown in Table 1.
[0112] Table 1 Tensile strength and compressive strength of the hydrogels of Example 1 and Comparative Examples 1-2
[0113]
[0114] As can be seen from Table 1, the hydrogel prepared according to the raw materials and method of Example 1 has better tensile strength and compressive strength. The tensile strength is more than 1500% of the ordinary hydrogel in Comparative Example 2, and the compressive strength can reach more than 97 MPa and can recover a certain shape.
[0115] (3) Testing the water retention rate of the hydrogels of the examples and comparative examples The water retention rate is calculated as the ratio of the remaining weight of the hydrogels of the examples and comparative examples to the initial weight during the test period under natural room temperature conditions.
[0116] Figure 8 The water retention rate change curve of the hydrogels of Examples 1 to 4 and Comparative Example 1 within 30 days is shown in FIG. Fig. 9 It is a partial enlarged view of the water retention rate change curve of the hydrogels of Examples 1 to 4 and Comparative Example 1 within 30 days. Figures 8-9 It can be seen that compared with the uncoated hydrogel in comparative example 1, the hydrogels in examples 1 to 4 covered with latex films have significantly better water retention effects, and the water retention rate can still reach more than 99% after 30 days.
[0117] The specific data of the water retention rate of the hydrogels of Examples 1 to 4 and Comparative Example 1 within 30 days are shown in Table 2.
[0118] Table 2 Water retention rate of hydrogels in Examples 1 to 4 and Comparative Example 1
[0119]
[0120] As can be seen from Table 2, the hydrogels prepared by the raw materials and methods of Examples 1 to 4 have good water retention effects, and the water retention rate can still reach more than 99% after 30 days. The surface of the hydrogel in Comparative Example 1 is not coated, so the water retention effect is poor, and its water retention rate on the third day is significantly reduced, which seriously affects its mechanical properties and service life.
[0121] It can be seen from the above embodiments and comparative examples that, compared with ordinary hydrogels without cement hydration product nanoparticles, the coated polymer hydrogel of the present invention has better mechanical properties, the tensile strength can reach 400kPa, the compressive strength can reach more than 90MPa and the shape can be kept basically unchanged, and the deformation rate is only 6.4%. After repeated stretching, the coated polymer hydrogel of the present invention has a good shape recovery effect and a low deformation rate. Except for the first stretching, the deformation rates of other stretchings are kept below 10%. Compared with the uncoated polymer hydrogel, since the surface of the coated polymer hydrogel of the present invention is covered with a latex film formed by polyvinyl acetate emulsion, its water retention rate is still above 99% after 30 days, which is conducive to the stable maintenance of various properties of the polymer hydrogel and a significant extension of the service life.
[0122] In summary, the present invention introduces cement hydration product nanoparticles into the polymer monomer, which is beneficial to the formation of physical cross-linking to improve the mechanical properties and water retention, and combines the outer film layer made of polyvinyl acetate emulsion to achieve high water content and stable performance of the hydrogel, thereby obtaining a coated polymer hydrogel material with high strength, good toughness, good water retention and long service life.
Claims
1. A film-coated polymer hydrogel, characterized in that: It comprises a polymer hydrogel matrix and an outer film layer; the outer film layer is coated on at least a part of the surface of the polymer hydrogel matrix; The polymer hydrogel matrix comprises the following preparation raw materials: polymer monomer, cement hydration product nanoparticles, initiator and water; The raw material for preparing the outer film layer includes latex.
2. The film-coated polymer hydrogel according to claim 1, characterized in that: The water content of the film-coated polymer hydrogel is 50-95%.
3. The film-coated polymer hydrogel according to claim 1, characterized in that: The latex includes at least one of polyvinyl acetate latex, polybutadiene latex or styrene-butadiene latex; And / or, the polymer monomers include acrylamide monomers, acrylate monomers or a combination thereof; And / or, the initiator includes at least one of a persulfate initiator, an azo initiator or a peroxide initiator.
4. The film-coated polymer hydrogel according to claim 1, characterized in that: The cement hydration product nanoparticles are formed by a hydration reaction between cement and water under the action of external mechanical force and low temperature conditions; the low temperature is -2 to 5°C; preferably, the cement includes at least one of fast-hardening silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, fly ash silicate cement or composite silicate cement.
5. The film-coated polymer hydrogel according to claim 1, characterized in that: The mass ratio of the polymer monomer to the cement hydration product nanoparticles is 100:(0.1-5); and / or, the mass ratio of the polymer monomer to the initiator is 100:(0.05-1); And / or, the mass ratio of the polymer monomer to the water is 100:(100-1000).
6. The film-coated polymer hydrogel according to claim 1, characterized in that: The raw materials for preparing the polymer hydrogel matrix also include a co-initiator and / or a cross-linking agent; the co-initiator is preferably an amine co-initiator; the cross-linking agent is preferably an acrylamide cross-linking agent.
7. A method for preparing a film-coated polymer hydrogel, characterized in that: The following steps are involved: Mixing polymer monomers, cement, initiator and water under mechanical external force and low temperature conditions, wherein the low temperature is -2 to 5°C; Then, the temperature is raised to carry out polymerization reaction to obtain a polymer hydrogel matrix; latex is applied on the surface of the polymer hydrogel matrix to form an outer film layer to obtain the film-coated polymer hydrogel according to any one of claims 1 to 6.
8. The preparation method according to claim 7, characterized in that: The polymerization reaction temperature is 15 to 35° C. And / or, the polymerization reaction time is 1 to 15 hours.
9. The preparation method according to claim 7, characterized in that: The latex is applied to the surface of the polymer hydrogel matrix in a manner including at least one of coating, spraying or dipping.
10. Use of the coated polymer hydrogel according to any one of claims 1 to 6 in the preparation of tissue engineering materials, drug delivery materials, software robots, wearable devices or artificial joints.